FAKTOR – FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN NON–KEUANGAN YANG TERDAFTAR DI BEI - ISTIMAWANI, ELISABETH TRI ARYANTI (E-Jurnal Akuntansi TSM, 2021)
The purpose of this study was to examine and obtain empirical evidence whether the intangible assets, debt policy, dividend policy, liquidity ratio, profitability ratio, activity ratio, managerial ownership, and firm size on firm value. This research uses data from 59 non-financial companies listed on the Indonesia stock exchange (IDX) from the period 2014 to 2016. Data for this study were selected using purposive sampling method. The data in the model were analyzed using hypothesis method with multiple regression. The results of this research show that debt policy, dividend policy and profitability ratio have a significant effect on firm value, while intangible assets, liquidity ratio, activity ratio, managerial ownership and firm size doesn’t have significant effect on firm value.